IDENTIFIKASI KEANEKARAGAMAN JENIS BIVALVIA DI PANTAI WALAKIRI SUMBA TIMUR - Ina, Anita Tamu (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
The purpose of this study was to determine the diversity of Bivalves in the tidal area of Walakiri Beach, East Sumba Regency. The method used is descriptive quantitative method. The sampling technique in this study used a purposive sampling technique and the sample was taken using the transect method combined with the quadrant (m2) method. The results of this study were found 299 individuals from 9 species, namely, Tellina puchella, Leukoma staminea, Anadara antiquata, Gefrarium pectinatum, Potamocorbula faba hinds, Fragum unedo, Hiatula diphos, Vasticardium subrogosum, and Meretrix meretrix. The highest density value was in the species Potamocorbula faba hinds, namely 7.407 with a frequency value of 0.296, while the lowest density was in Hiatula diphos, namely 0.037 with a frequency of 0.012. Based on the number of species and the density value of the bivalve diversity index in the tidal area of Walakiri Beach, it was 1.053 in the medium category.